Tomografía axial computarizada y resonancia magnética para la elaboración de un atlas de anatomía segmentaria a partir de criosecciones axiales del perro (2006)
ABSTRACT: This article describes the process of creation of a digital atlas of canine anatomy by criosectioning with computed tomography and magnetic resonance. The atlas is intended to be of help for students and practitioners. A medium size, adult, healthy creole, black colored bitch was used, weighing 22 Kg.Computed tomography and magnetic resonance were performed at the San Vicente de Paul Hospital and at the Instituto de Alta Tecnología Médica de Antioquia (IATM), respectively. Segmentary images (frontal, sagital and transverse) of the complete body were obtained and analyzed by comparison with real cuts of the dog’s body. Besides its use for the atlas these images are available in the animal anatomy laboratory at the Universidad de Antioquia.